The exotic wasp Megastigmus transvaalensis (Hymenoptera: Torymidae): first record and damage on the Brazilian peppertree, Schinus terebinthifolius drupes, in Sao Paulo, Brazil - Ferreira-Filho, Pedro J.; Pina-Rodrigues, Fatima C. M.; Silva, Jose M. S.; Guerreiro, Julio C.; Ghiotto, Thais C.; Piotrowski, Ivonir; Dias, Luiz P.; Wilcken, Carlos F. [UNESP]; Zanuncio, Jose C. (Acad Brasileira De Ciencias, 2015)
This paper records the first report of Megastigmus transvaalensis Hussey (Hymenoptera: Torymidae) in Brazilian peppertree, Schinus terebinthifolius Raddi (Anacardiaceae) drupes in Sorocaba, state of Sao Paulo, Brazil. This wasp is an invasive species and was found damaging S. terebinthifolius drupes in urban areas (35.0+/-15.8%), natural forests (21.5+/-10.2%) and restoration areas (15.8+/-8.4%). The bio-ecology and damage caused by M. transvaalensis in the S. terebinthifolius drupes warrants further study focused upon the management of this phytophagous wasp. Megastigmus transvaalensis has a potential to be disseminated throughout Brazil and is posing a threat to the natural regeneration of S. terebinthifolius in the native forests and restoration areas and ecological regions of this country.
Keywords: Anacardiaceae; biological control; forest pest; monitoring; restoration